플라스틱 광섬유를 이용한 호흡센서의 개발 - 유욱재; 백지윤; 조동현; 장경원; 서정기; 허지연; 이봉수; 조영호; 박병기; 문주현; Yoo, Wook-Jae; Baek, Ji-Yun; et al. (Journal of biomedical engineering research, 2009)
In this study, we fabricated a plastic optical fiber based sensor which can monitor the respiration of a patient. The circumference changes of the abdomen were measured using a mirror, a light source and optical detectors because the circumferences of the abdomen could be varied with respiration. The intensity of the reflected lights were measured according to the changes of distance between mirror and plastic optical fiber connected to a light source and a photodiode-amplifier system using a Y-coupler. The respiration signals of fiber-optic sensor system were compared with those of the respiratory and temperature transducers of the $BIOPAC^{(R)}$ system. It is expected that a fiber-optic respiration sensor could be developed for real time respiration monitoring during MRI procedure based on this study.